EMPIRICAL PREDICTION OF PERMEABILITY DISTRIBUTION BY INTEGRATING STATIC - DYNAMIC RESERVOIR MODEL, AND TRACER TEST DATA LAYER Z600 KEUTAPANG FORMATION, RANTAU FIELD, NORTH SUMATRA SUB-BASIN, NORTH SUMATRA - NUR ARDIANTO (NIM : 22012309), REZA
Rantau structure is a faulted anticline that extends Southeast - Northwest. Rantau structure has 3.5 km width, 11 km long and 400 m closure height. Rantau structure was deposited in distal bar, mouth bar, distributary channel and interdistributary channel in fluival dominated delta depositional environment. Connectivity test was carried out on the layer Z600 tracer in block C1 and C2 in 6 injection wells, while the analysis carried out on 6 production wells, the purpose is to validate the results of the static reservoir modeling. Facies modeling validation was performed by integrating the static reservoir modeling with tracer test data. The analysis was conducted by creating segments for area of injection and production wells. Facies analysis was integrated with tracer test results to show a correlation between rapid propagation of the fluid with facies distribution. Facies modeling validation was performed by integrating the relationship between oil cumulative distribution map, gas and water in Z600 with facies distribution. The relationship shows that at the bottom side of the structure which has a tendency facies form Medium Coarse & Fine - Medium, provide higher cumulative production when compared on the upper side which has the upper part has a tendency facies in the form of very fine sand. Breakthrough time modeling results of static - dynamic reservoir has a tendency faster than tracer test results. This indicates static reservoir modeling using the correlation equations porosity permeability tends to be optimistic. To get a static modeling of reservoir permeability distribution close tracer test results, then the creation of a correction factor equations that correlate the time difference breakthrough and data cross plot porosity and permeability. Results of the integration of static reservoir modeling, dynamic reservoir modeling and tracer test data can be carried out to obtain equations to accommodate the amount of permeability at static modeling to match the reality on the ground tracer test results.